Pemanfaatan Sampah Plastik Melalui Ecobrick Menjadi Plang Nama Nagari Guguak Malalo - Esy Maestro; Hanifiyah Zahra; Aidil. M; Anisa Aulia Syakila; Olivia Aulandari (CV. ITTC INDONESIA, 2025)
The problem raised in this study is how the process of making ecobricks into nameplates for Nagari Guguak Malalo. This problem arises from the condition of the nagari community who still face problems in managing plastic waste, which is generally done by burning, as well as their still minimal knowledge about ecobricks. The process of making this nagari nameplate consists of 12 stages, namely: collection, cleaning, washing, drying, cutting, insertion, compaction, design and ordering, painting, arrangement, installation, and inauguration. This study aims to change the habits of the nagari community in managing plastic waste, which initially burned plastic waste then changed to not burning plastic waste anymore and preferring to turn the plastic waste into items that have utility value and also to increase the knowledge of the community in the nagari about ecobricks. The method used consists of 4 main methods which include direct observation, interviews, socialization, and data analysis. The analysis technique used is thematic analysis, which is carried out by identifying, grouping, and interpreting the main themes from the data from observations, interviews, and socialization. The results of the study showed that the village nameplate with the words